Strategie wspomagania rozwoju umiejętności manualnych dzieci w wieku przedszkolnym i wczesnoszkolnym - Wójcik, Magdalena (Studia Edukacyjne, 2021)
The development of fine motor skills in preschool and early school age children is a difficult and long process, and its disturbance may not only lead to serious problems with the process of drawing or writing, but also disrupt the purely academical learning. That is why it is so important to take into account the overall effects of improving manual skills, the specificity of the child’s perceptual and motor functioning at a given stage of development and to respect the key elements of the diagnostic and improvement strategy.